Science podcasts: analysis of global production and output from 2004 to 2018 - MacKenzie, Lewis E. (Royal Society open science, 2019)
Since 2004, podcasts have emerged as a decentralized medium for science communication to the global public. However, to date, there have been no large-scale quantitative studies of the production and dissemination of science podcasts. This study identified 952 English language science podcasts available between January and February 2018 and analysed online textual and visual data related to the podcasts and classified and noted key production parameters. It was found that the total number of science podcast series available grew linearly between 2004 and 2010, and then exponentially between 2010 and 2018. Sixty-five per cent of science podcast series were hosted by scientists and 77% were targeted to public audiences. Although a wide range of primarily single-subject science podcasts series were noted, 34% of science podcast series were not dedicated to a science subject. Compared to biology and physics, chemistry may be under-represented by science podcasts. Only 24% of science podcast series had any overt financial income. Sixty-two per cent of science podcast series were affiliated to an organization; producing a greater number of episodes (median = 24, average = 96) than independent science podcast series (median = 16, average = 48). This study provides the first ‘snapshot’ of how science podcasts are being used to communicate science to public audiences around the globe.